Wavelength‐dispersive dark‐field contrast: micrometre structure resolution in neutron imaging with gratings. Issue 2 (18th March 2016) - Strobl, M.; Betz, B.; Harti, R. P.; Hilger, A.; Kardjilov, N.; Manke, I.; Gruenzweig, C.
Abstract : This article describes experimental work demonstrating how dark‐field neutron imaging can provide quantitative characterization of structures in the micrometre range which are not amenable to direct real space resolution. Abstract : Dark‐field imaging using grating interferometers has been proven to have a high potential for applications in engineering, magnetism, and soft matter and biophysics, as well as in medicine with both neutrons and X‐rays. The access to spatially resolved small‐angle scattering information in neutron dark‐field imaging provides information about structures beyond direct spatial image resolution. The dark‐field contrast modality is hence a valuable tool for materials science based on neutron imaging. This is underlined by the success of the method, despite its current limitation to qualitative scattering information. Here it is demonstrated how a wavelength‐dispersive approach allows such drawbacks to be overcome by providing quantitative structure size information and hence can introduce novel possibilities and insights for materials science.